Pandangan dan Sikap Akuntan Publik terhadap Fenomena Expectation Gap dan Tanggung Jawab Hukum Auditor - Mirdah, Andi; Yuliati, Yuliati; Irianto, Gugus (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2007)
In the development, public accounting profession exposed to a challenge where there is expectation gap between auditor and society as a service user. Some case involving public accountant and society misunderstanding to the responsibility and role of public accounting depicts the expectation gap. The widening of expec¬tation gap also fostered by profession motivation in protecting himself to deviate society stress and to decrease legal liability to auditor (OSullivan, 1993). Gener¬ally, the existing research, examining perception of auditor and user of audited financial report related to expectation gap issues, use positivistic approach. This qualitative research aims to get an deep understanding of overview and attitude of public accountant and their professional staff to the expectation gap phenom¬ena that happened between public accounting and user financial report, specially the client of public accountant itself and how the point of view and public account¬ing attitude in perceiving their liability in practice. Keyword: Expectation Gap, Simbolic Interacsionism, Audiors’ Legal Liability